Validity and Practicality of Ethnoprinting Media for Inventorying Fern Diversity in West Kalimantan - Herditiya Herditiya; Tesa Manisa (Jurnal Penelitian Pendidikan IPA, 2026)
Ferns grow abundantly in humid and suitable areas in the land of West Kalimantan. However, the problem is that students have not been able to differentiate the classification of ferns and distinguish what cormus plants and thallus plants are. Therefore, one of the media that supports students’ understanding of ferns is ethnoprinting. The purpose of this study was to determine the diversity of West Kalimantan ferns and to determine the feasibility of ethnoprinting learning media, seen from the validity and practicality of the product. This study used the ADDIE development model, and the sampling technique used purposive sampling, with a small-scale sample of 20 people and a large-scale sample of 59 people. The results of the study showed that the diversity of ferns found was 29 species, consisting of 3 classes and 16 families, and the results of the development of ethnoprinting fern products from the percentage of media experts were 84 % and material experts were 81% with very valid criteria, while the practicality response on a small scale was 81% and the practicality response on a large scale was 82% with very practical criteria. Therefore, these results indicate that the development of ethnoprinting products is valid and practical and can be used for teaching fern material.